Creative accounting from an Islamic perspective: viewed from sadd al dzari’ah concept - Istiariani, Irma; Wahyuni, Andi Sri; Amalia, Farah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Purpose - This study aims to determine how Islamic Perspective views creative accounting practices that have been happening in Indonesia if viewed from the Sadd Al dzari`ah ConceptMethod - The method used in this research is qualitative with a library research approach. The case discussed in this study is creative accounting conducted by many companies in Indonesia, as viewed from the Sadd Al dzari`ah Concept.Result - The results of this study shows that creative accounting practices in many companies in Indonesia are not follow Islamic perspectives if viewed from the Sadd Al dzari`ah Concept.Implication - This research emphasizes that management should always identify all creative accounting techniques to avoid the occurrence of creative accounting.Originality - Similar research related to creative accounting has been conducted. Still, the research about creative accounting has been widely reviewed from the Islam perspective, especially Sadd Al dzari`ah concept, which has never been done. This research contributes to how creative accounting practices are viewed from the Islamic prespective, especially from the Sadd Al dzari`ah concept.